2012
DOI: 10.1186/1471-2105-13-s13-s9
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical property consensus sequences for functional analysis, design of multivalent antigens and targeted antivirals

Abstract: BackgroundAnalysis of large sets of biological sequence data from related strains or organisms is complicated by superficial redundancy in the set, which may contain many members that are identical except at one or two positions. Thus a new method, based on deriving physicochemical property (PCP)-consensus sequences, was tested for its ability to generate reference sequences and distinguish functionally significant changes from background variability.MethodsThe PCP consensus program was used to automatically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Many studies have demonstrated that consensus predictions could outperform single sequence determination method in vaccine design (Mallios, 2003; Moutaftsi et al, 2006; Yan et al, 2007). Importantly, not only conserved regions but also variable sites could be incorporated in the consensus sequences, and such design does not seem to alter structural and functional properties of target protein on a given location (Schein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that consensus predictions could outperform single sequence determination method in vaccine design (Mallios, 2003; Moutaftsi et al, 2006; Yan et al, 2007). Importantly, not only conserved regions but also variable sites could be incorporated in the consensus sequences, and such design does not seem to alter structural and functional properties of target protein on a given location (Schein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This means that they may be selectively excised during generation of subgenomic RNAs or resumption of active growth after latent periods. Thus, rational reference sequences of viruses should be based on those obtained from direct isolates of diseased tissue or consensus sequences covering many isolates [ 111 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is designed to be useful for sets with many sequences (such as viral isolates) that have a high superficial redundancy (i.e., nearly identical sequences that differ at only a few positions). The rationale and details of the method are described in detail elsewhere (Bowen et al, 2012; Danecek et al, 2010; Danecek and Schein, 2010; Schein et al, 2012). Here, the PCP-con program was used to determine a consensus of 31 of the most diverse EV VPg sequences (Figure 1).…”
Section: Methodsmentioning
confidence: 99%